2017
DOI: 10.1021/acsami.6b13570
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride Nanosheet-Anchored Pd–Fe Core–Shell Nanoparticles as Highly Efficient Catalysts for Suzuki–Miyaura Coupling Reactions

Abstract: Boron nitride nanosheets (BNNS) were used to anchor bimetallic Pd-Fe nanoparticles for Suzuki-Miyaura coupling catalysts. The bimetallic nanoparticles were found to be core-shell in structure, and their formation was likely facilitated by their interactions with the BNNS. The Pd-Fe/BNNS catalysts were highly effective in representative Suzuki-Miyaura reactions, with performances matching or exceeding those of the state-of-the-art methods. Specifically, the superior catalytic activities were characterized by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 63 publications
1
39
0
Order By: Relevance
“…Moreover, computational studies have indicated that atoms of metals such as Au, Cu, and Mo on defective h‐BN could be active electrocatalysts for CO oxidation or nitrogen fixation . From experimental studies, it is proposed that both precious and non‐precious metal nanoparticles on highly defective h‐BN nanosheets are excellent systems for the electrocatalysis of CO oxidation, for the hydrogenation of nitroaromatics, for the Suzuki–Miyaura reaction, and for the Fischer–Tropsch synthesis …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, computational studies have indicated that atoms of metals such as Au, Cu, and Mo on defective h‐BN could be active electrocatalysts for CO oxidation or nitrogen fixation . From experimental studies, it is proposed that both precious and non‐precious metal nanoparticles on highly defective h‐BN nanosheets are excellent systems for the electrocatalysis of CO oxidation, for the hydrogenation of nitroaromatics, for the Suzuki–Miyaura reaction, and for the Fischer–Tropsch synthesis …”
Section: Introductionmentioning
confidence: 99%
“…The resultant Pd/BNNS catalyst exhibited high catalytic activity and recyclability towards hydrogenation of nitro aromatics. Further, Lu and co‐workers reported BNNS‐anchored bimetallic PdFe NPs (PdFe/BNNS) by a chemical reduction method using NaBH 4 as the reducing agent and explored its catalytic activity towards the Suzuki–Miyaura coupling reaction . The TEM and energy‐dispersive X‐ray spectroscopy (EDS) analysis revealed that Pd–Fe core–shell NPs with relatively thick Fe shells were anchored on or close to the defective edges of the BNNS.…”
Section: Two‐dimensional Materials As Catalyst Supportsmentioning
confidence: 99%
“…In comparison, the heterogeneous catalysts of Pd clusters or nanoparticles (NPs) on solid supports may overcome these limitations and thus have been paid much attention. [7][8][9][10] Nonetheless, these heterogeneous catalysts usually suffer from less exposed active sites and limited accessibility for reactants, compared with their Single-atom (SA) catalysis bridging homogeneous and heterogeneous catalysis offers new opportunities for organic synthesis, but developing SA catalysts with high activity and stability is still a great challenge. Herein, a heterogeneous catalyst of Pd SAs anchored in 3D ordered macroporous ceria (Pd-SAs/3DOM-CeO 2 ) is developed through a facile template-assisted pyrolysis method.…”
Section: Introductionmentioning
confidence: 99%